Nitrogen-doped carbon dots originating from unripe peach for fluorescent bioimaging and electrocatalytic oxygen reduction reaction - Atchudan, Raji; Edison, Thomas Nesakumar Jebakumar Immanuel; Lee, Yong Rok (Journal of colloid and interface science, 2016)
This paper reports the robust hydrothermal synthesis of N-CDs using the unripe fruit of peach as the carbon precursor and aqueous ammonia as the nitrogen source. The synthesized N-CDs exhibits a good catalytic activity in an alkaline medium (0.1M KOH) with remarkable ORR and highly biocompatible thus it can be used as fluorescence imaging probes. [Display omitted] This paper reports the robust hydrothermal synthesis of nitrogen doped carbon dots (N-CDs) using the unripe fruit of Prunus persica (peach) as the carbon precursor and aqueous ammonia as the nitrogen source. The optical properties of synthesized N-CDs were characterized by ultraviolet visible (UV–Vis) and fluorescence spectroscopy techniques. The synthesized N-CDs were emitted blue light when excitated with a portable UV lamp. The materials with the optical properties were characterized further by high resolution transmission electron microscope (HRTEM), X-ray diffraction (XRD), Raman, Fourier transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS). The mean size of the N-CDs was approximately 8nm, as calculated from the HRTEM image. The d-spacing of N-CDs, calculated using Bragg law, was approximately 0.21nm, which was consistent with the interlayer distance calculated from the HRTEM image. FT-IR spectroscopy and XPS revealed the presence of the phytoconstituents functionalities of peach fruit over the N-CDs surface and a high level of nitrogen doping on carbon dots (CDs) was confirmed by XPS studies. These results suggest that the unripe fruit extract of peach is an ideal candidate for the preparation of N-CDs. The resulting N-CDs showed excellent optical properties in water. The synthesized N-CDs exhibited a high fluorescence quantum yield and low cytotoxicity, and can be used as fluorescence imaging probes. In addition, the N-CDs were catalytically activite towards the oxygen reduction reaction (ORR). The N-CDs exhibited good catalytic activity in an alkaline medium (0.1M KOH) with a remarkable ORR of approximately 0.72V vs reversible hydrogen electrode (RHE), and O2 reduction follows mainly a 2 electron pathway by being reduced to hydrogen peroxide. The 2-electron reduction pathway is used in industry for H2O2 production.